Leadership and Work Environment Influence on Employee Performance of PT Pegadaian Syariah CPS Meulaboh - Putra, Yudha Prawira Junistiara; Marisa, Rita (Lembaga Riset Mutiara Akbar (LARISMA), 2024)
The author chose the location for this research, namely PT Pegadaian Syariah CPS Meulaboh. From the entire population, the author chose 15 employees as respondents in this research. The hypothesis in this research is that it is thought that there is a positive and significant influence between leadership variables and the work environment on employee performance variables. After testing the hypothesis by carrying out a multiple linear regression test, the results are: Based on the results of the t test (partial test) for variable X1, the sig value was obtained, namely 0.910>0.05. So in this case it means that variable X1 (Leadership) has no effect on variable Y (Employee Performance). For the variable X2, the sig value is 0.875>0.05. So in this case it means that variable X2 (Work Environment) also has no effect on variable Y (Employee Performance). Based on the results of the F ANOVA test (simultaneous test) for variables X1 and X2, the sig value was obtained, namely 0.962 > 0.05. So in this case it means that variables X1 and X2 simultaneously (together) have no effect on variable Y. So it can be concluded that the hypothesis is rejected.